Achieving human development objectives through microfinance institution: the case of Amanah Ikhtiar Malaysia - Md Saad, Norma (Islami Bank Training and Research Academy, 2010)
Human development (HD), according to Ranis and Stewart (2000) is defined as the enhancement of the human situation so that people enjoy longer, healthier, and more meaningful lives. Some aspects of HD are related to people’s physical well-being, such as health, nutrition, and education. Other aspects of HD encompass widening of choice and enhanced empowerment, which include participation, political freedoms and cultural aspects. This study looks the role of a microfinance institution, Amanah Ikhtiar Malaysia (AIM), in promoting human development among the rural poor in Malaysia. A survey was conducted to analyze AIM members’ evaluation about the achievement of certain goals of human development since becoming members of AIM. The study also analyzes various training programs and activities adopted by AIM to successfully achieve its target in human development among the rural poor in Malaysia. The results of this study indicate that AIM, through its microcredit and training activities, has been able to alleviate poverty, improve health condition of it members, as well as enable its members to improve the education level of their children.